Recent progress of aptamer‒drug conjugates in cancer therapy - Jiaxuan He; Qiao Duan; Chunyan Ran; Ting Fu; Yuan Liu; Weihong Tan (Acta Pharmaceutica Sinica B, 2023)
Aptamers are single-stranded DNA or RNA sequences that can specifically bind with the target protein or molecule via specific secondary structures. Compared to antibody-drug conjugates (ADC), aptamer‒drug conjugate (ApDC) is also an efficient, targeted drug for cancer therapy with a smaller size, higher chemical stability, lower immunogenicity, faster tissue penetration, and facile engineering. Despite all these advantages, several key factors have delayed the clinical translation of ApDC, such as in vivo off-target effects and potential safety issues. In this review, we highlight the most recent progress in the development of ApDC and discuss solutions to the problems noted above.